Integration through Control: the Model of Power Hijacking as an Alternative View on European Union Integration (Economic and Political Thought, 2018)
The following paper presents a possible new explanation for theEuropean Union’s turbulent integration. By combining elements of gametheory, neo-functionalist theory and its neo-realist account as well as devotingspecial attention to liberal intergovernmentalism it presents a method ofthinking about the way in which European states function and calculate theirbehaviours in relation to integration efforts. Through that it attempts to buildan initial framework for an alternative way of thinking about integrationand disintegration of the European Union. Countries attempt to controlone another through products of a centralised political process, imposinglimitations on freedom of action of others: the more control, the less freedomof action and the more integration as a result. The same mechanism canbe both responsible for tendencies of integration as well as disintegration,since countries that fail to increase their ability to control others see that asan asymmetrical gain for others, and tend to opt out from integration, or todisassociate themselves from the project altogether.
Keywords: integration, European union, game theory